Alterations of the Innate Immune System in Susceptibility and Resilience After Social Defeat Stress - Ambrée, Oliver; Ruland, Christina; Scheu, Stefanie; Arolt, Volker; Alferink, Judith (Frontiers in Behavioral Neuroscience, 2018)
Dysregulation of innate immune responses has frequently been reported in stress-associated psychiatric disorders such as major depression. In mice, enhanced circulating cytokine levels as well as altered innate immune cell numbers have been found after stress exposure. In addition, stress-induced recruitment of peripheral monocytes to the brain has been shown to promote anxiety-like behavior. However, it is yet unclear whether specific differences in the innate immune system are associated with stress susceptibility or resilience in mice. Utilizing chronic social defeat, a model of depression and stress vulnerability, we characterized peripheral and brain-invading myeloid cells in stress-susceptible and resilient animals. In all defeated animals, we found reduced percentages of CD11c+ dendritic cells (DCs) by flow cytometry in the spleen when compared to non-defeated controls. Exclusively in susceptible mice conventional DCs of the spleen showed up-regulated expression of MHC class II and co-stimulatory CD80 molecules pointing toward an enhanced maturation phenotype of these cells. Susceptible, but not resilient animals further exhibited an increase in inflammatory Ly6Chi monocytes and higher numbers of spleen-derived CD11b+ cells that produced the proinflammatory cytokine tumor necrosis factor (TNF) upon lipopolysaccharide (LPS) stimulation. Increased percentages of peripheral CD45hi CD11b+ cells immigrated into the brain of defeated mice, regardless of resilience or susceptibility. However, cellular infiltrates in the brain of susceptible mice contained higher percentages of CC chemokine receptor 2 (CCR2+) Ly6Chi monocytes representing an inflammatory phenotype. Thus, we defined specific stress-related immune signatures involving conventional DCs and inflammatory Ly6Chi monocytes in susceptible and resilient mice. Together, our findings suggest an impact of the innate immune system in vulnerability to stress-related disorders such as major depression.